Moving beyond input legitimacy: When do democratic innovations affect policy making? - Thamy Pogrebinschi; Matt Ryan (European Journal of Political Research, 2018)
This article makes three key contributions to debates surrounding the effectiveness of democratic innovation, deliberation and participation in representative political systems. In the first instance, it argues that more attention should be paid to the role that participation actually plays in governance. The literature on democratic institutional design often neglects concern about the effects of innovative institutional designs on more traditional representative fora, at the expense of concerns about their internal procedures. Second, the article argues that despite limitations, replicable systematic comparison of the effects of institutional design is both necessary and possible even at the level of national governance. A comparative analysis of 31 cases of National Public Policy Conferences (NPPCs) in Brazil is presented. Finally, the article shows that popular deliberative assemblies that vary in their familiarity and their policy area of interest, and that organise their structure and sequence deliberation in different ways can be associated with differential effects on both option analysis and option selection stages of the policy process, respectively.
Keywords: 330; democratic innovations; deliberation; participation; effectiveness; national public policy conferences